Redonner visage aux gueules cassées. Sculpture et chirurgie plastique pendant et après la Première Guerre mondiale - Ackerman, Ada (RACAR : Revue d'art canadienne / Canadian Art Review, 2016)
During the First World War, French, British, and US sculptors dedicated their creative practice and knowledge to making masks for soldiers with facial injuries, thus allying art and science in an attempt to restore the most essential aspect of the soldiers’ identities. As artistic resources were mobilized to counter the destructive effects of the war, this new kind of sculpture engendered myths and fantasies about the artists’ power. This article argues that ultimately, though, the practice of mask-making was used as a strategy that benefitted the preservation of the prevailing economic and social order.